Наявність шкоди як умова відповідальності в сімейному праві - Єфремова, І. О.; Yefremova, I. О.; ORCID: http://orcid.org/0000-0002-2542-6812 (Право.uа. – 2019. – № 1. – С. 178-184, 2019)
У статті розглянуто таку умову відповідальності в сімейному праві як наявність шкоди. Обґрунтовано, що наявність матеріальної та (або) моральної шкоди не є обов’язковою умовою відповідальності в сімейному праві. Встановлення наявності матеріальної та (або) моральної шкоди необхідне у випадках, визначених договором або законом. Сімейний кодекс України передбачає право на відшкодування матеріальної та моральної шкоди лише в семи випадках. Доведено, що визначення розміру відшкодування завданої моральної шкоди порушенням сімейних прав та інтересів повинно здійснюватися за правилами Цивільного кодексу України. The author of the article has studied such a condition for liability within family law as the occurrence of harm. It has been substantiated that the occurrence of pecuniary and (or) moral damage is not a prerequisite for liability in family law.

The establishment of pecuniary and (or) moral damage is necessary in cases specified by the contract or by law. It has been argued that the right to compensation for pecuniary and moral damage is provided by the Family Code of Ukraine in the following cases: 1) if the moral harm was caused by the deprivation of a woman’s ability to give birth to a child (reproductive function) in regard to the exercise of her constitutional, official, labor duties or as a result of unlawful conduct towards her; 2) if the moral harm was caused by the deprivation of a man’s ability to exercise reproductive function in regard to the exercise of his constitutional, official, labor duties or as a result of unlawful conduct towards him; 3) if the pecuniary and moral damage was inflicted on the second parent in case of evasion of the parent, who lives with the child, from the implementation of the contract on exercising parental rights and the performance of duties by those who live separately from the child; 4) if the pecuniary and moral damage was caused to the parent who lives separately from the child, in case of evasion from the execution of the decision of the guardianship and care agency about the definition of the ways to participate in the upbringing of the child and communication with the child from the parent who lives separately from the child; 5) if the pecuniary and moral damage was caused to the parent who lives separately from the child, in case of evasion of the person from execution of the court decision on the definition of the ways of participation in the upbringing of the child and communication with the child from the parent who lives separately from the child; 6) if the pecuniary and moral damage was caused to the person with whom the minor child lived, in case of a spontaneous change of the minor child’s place of residence by the person; 7) if the pecuniary damage was caused by improper performance by parents of their responsibilities regarding the management of the child’s property. It has been proved that determination of the amount of compensation for moral harm caused by violations of family rights and interests should be carried out in accordance with the rules of the Civil Code of Ukraine.

В статье рассматривается такое условие ответственности в семейном праве как наличие вреда. Обосновано, что наличие материального и (или) морального вреда не является обязательным условием ответственности в семейном праве. Установление наличия материального и (или) морального вреда необходимо в случаях, определенных договором или законом. Семейный кодекс Украины предусматривает право на возмещение материального и морального вреда только в семи случаях. Доказано, что определение размера возмещения причиненного морального вреда нарушением семейных прав и интересов должно осуществляться по правилам Гражданского кодекса Украины.
Єфремова І. О. Наявність шкоди як умова відповідальності в сімейному праві / Єфремова Ірина Олексіївна // Право.uа. – 2019. – № 1. – С. 178-184.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Сімейне право. Family law. Семейное право; відповідальність у сімейному праві; наявність шкоди; матеріальна шкода; моральна шкода; шкода; ответственность; семейное право; наличие вреда; материальный вред; моральный вред; вред; responsibility within family law; family law; occurrence of harm; condition for liability; pecuniary damages; moral harm